Bahasa Indonesia: english - Hanafi, Naufal; Rustam, Rusli (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2020)
Cabbage crop caterpillar (Crocidolomia pavonana Fabricius) is the primary pest on cabbage. This study aimed to know the toxicity of noni seed extract (Morinda citrifolia Linnaeus) against C. pavonana. This study used a completely randomized design (CRD) with five treatments and four replications. The treatments given were the application of noni seed extract in different concentrations; 0, 25 g.l-1, 50 g.l-1, 75 g.l-1and 100 g.l-1. The parameters observed were initial death time, total mortality, daily mortality, lethal time 50, and lethal concentration. The results showed that noni seed extract was able to kill C. pavonana larvae. The higher the extract concentration, the more insects died, and the faster the time of death occurred. The concentration of LC50 was 6.7%, while LC95 was 23.5%. Keywords: Crocidolomia pavonana, noni crop, botanical insecticide